Pengaruh Sustainability Reporting Dan Corporate Social Responsibility Terhadap Nilai Perusahaan Dengan Pengungkapan Pengendalian Internal Sebagai Moderasi - Parade Natama; Hermie Hermie (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the influence of sustainability reports and corporate social responsibility in influencing company value by moderating internal control disclosures. This research uses a population consisting of companies that are part of the SRI-KEHATI Index in the period 2018 - 2022. The data taken from this sample is secondary data in the form of sustainability report disclosures in accordance with the 17 SDGS points, the amount of costs incurred for environmental development, disclosure Internal Control and net profit after tax obtained from the Company's Sustainability Report and Annual Report as well as share market value obtained through the IDX website (www.idx.co.id). Data was collected from 27 different companies with a total sample of 101 data using purposive sampling techniques. Data processing was carried out using the SPSS version 27 application and using the multiple regression analysis method. Based on the results of the analysis that has been carried out, it is concluded that the sustainability report has a significant positive effect and corporate social responsibility has a non-significant positive effect on company value, while environmental control moderation has a significant positive strengthening effect on the sustainability report and a non-significant weakening effect on corporate social responsibility.